Proposal for intervention to qualify the registration of information in primary health care for people living with HIV in the municipality of Rio de Janeiro (Research, Society and Development, 2023)
The city of Rio de Janeiro has been marked in recent years by a significant change in the health care model. In this context, we have HIV infection, which is a serious condition considered one of the biggest health problems today. With the experience of institutional, it was possible to identify a difficulty in evaluating the medical records of people diagnosed with HIV infection due to incomplete records, about the conduct of the case and, others, with lack of clarity in information. The present study aimed to propose a set of minimum necessary information that must be described in the medical records of people living with HIV. As a method, a systematic review was carried out, including studies in all contexts such as primary care, specialized care, preferably observational studies and clinical trials, but without restrictions on the design. The process of tracking titles and abstracts was through the Rayyan program and independently conducted by two investigators, discrepancies were resolved by consensus with the consideration of a third investigator. We selected 24 articles and raised 16 relevant variables that were compared to the appropriate bibliography. In addition to developing a guiding document to support professionals in recording information, the present work will disseminate the results to the Municipal Health Department of Rio de Janeiro, contributing to the possibility of optimizing care in the care of PLHIV, adding quality, in addition to more data available for studies and evaluations.